Parasuicidal Patients in the Emergency Department and Their Relationship with Cannabinoid Gene Polymorphism - Yildiz, Mustafa; Kara, Murat; Bozdemir, Mehmet Nuri; Kara, Bilge; Goktekin, Mehmet Cagri; Gurbuz, Sukru; Emet, Mucahit (Kure Iletisim Grubu A S, 2012)
Background: Suicidal behavior represents a serious public health problem. Studies about twins, adoption, and family conflicts have shown a relationship between genetics and suicide. CB1 receptors are coded by the cannabinoid-1 receptor (CNR1) gene. It has been shown that CNR1 gene polymorphism (1359 G/A) is associated with many neuropsychiatric disorders, including major depression. Objective: Our aim was to study whether there was an association between the polymorphism of the CNB1 receptor and suicide attempts. We compared non-suicidal subjects with suicide-attempt victims to substantiate these findings. Materials and Methods: Peripheral blood samples were drawn from all of the participants and single nucleotide polymorphism (SNP) of the cannabinoid gene (1359 G/A) was analyzed. Results: The study included 115 suicide attempts (parasuicide patients) (mean age 25.6 +/- 8.5; 41 males, 74 females) and 69 unrelated healthy subjects (mean age 27.5 +/- 10.6; 38 males, 31 females). The genotype distributions were significantly different between the parasuicide and control groups and this difference was attributed to the AG genotype rates (21.7% vs 44.9%, p=0.001). Having the AG genotype lowered the admission to the ED due to parasuicide 3.3 times (95% CI: 1.6-6.8). The frequencies of A and G alleles in the CNR1 gene polymorphism were 16.1% (n=37) and 83.9% (n=193) in parasuicide patients and 22.5% (n=31) and 77.5% (n=107) in the control group, respectively (p=0.127). All the subjects with the AA genotype were in the parasuicide group (n=6).The frequency of the AG genotype was significantly lower in parasuicide patients with a previous psychiatric diagnosis compared to suicide attempts without a previous diagnosis (32% (n=8) vs. 68% (n=17); p=0.004). Conclusion: There is a preventive association between CNR1 rs1049353 (1359 G/A) gene polymorphism and parasuicide patients. CNR1 receptor polymorphism may be used as a biological test to help predict and prevent suicidal behavior if the relationship can be proved with further studies.
Acil serviste intihar girişimi hastaları ve bu hastaların kannabinoid gen polimorfizmi ile ilişkisi
Keywords: Suicide; polymorphism; CNR1; parasuicide; suicide attempt; suicidal behavior